2021
DOI: 10.3390/cancers13030480
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α3β1 Promotes Invasive and Metastatic Properties of Breast Cancer Cells through Induction of the Brn-2 Transcription Factor

Abstract: In the current study, we demonstrate that integrin α3β1 promotes invasive and metastatic traits of triple-negative breast cancer (TNBC) cells through induction of the transcription factor, Brain-2 (Brn-2). We show that RNAi-mediated suppression of α3β1 in MDA-MB-231 cells caused reduced expression of Brn-2 mRNA and protein and reduced activity of the BRN2 gene promoter. In addition, RNAi-targeting of Brn-2 in MDA-MB-231 cells decreased invasion in vitro and lung colonization in vivo, and exogenous Brn-2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
3
14
1
Order By: Relevance
“…Moreover, rescue of α3β1 expression in α3-Cr cells using a doxycyclineinducible α3 model had a minimal effect on the transcriptome, suggesting that use of CRISPR to eliminate α3β1 led to a cellular adaptation such that gene regulation was no longer responsive to the integrin. Interestingly, α3-Cr cells showed reduced cell invasion in vitro and impaired metastatic colonization in vivo compared with control cells, as we reported previously for RNAi-mediated suppression of α3β1 [12,13]. Our results identify a requirement for α3β1 in invasion and metastasis that is independent of its ability to regulate gene expression on a global scale.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…Moreover, rescue of α3β1 expression in α3-Cr cells using a doxycyclineinducible α3 model had a minimal effect on the transcriptome, suggesting that use of CRISPR to eliminate α3β1 led to a cellular adaptation such that gene regulation was no longer responsive to the integrin. Interestingly, α3-Cr cells showed reduced cell invasion in vitro and impaired metastatic colonization in vivo compared with control cells, as we reported previously for RNAi-mediated suppression of α3β1 [12,13]. Our results identify a requirement for α3β1 in invasion and metastasis that is independent of its ability to regulate gene expression on a global scale.…”
Section: Introductionsupporting
confidence: 83%
“…Previously, we showed that RNAi-mediated suppression of ITGA3 in MDA-MB-231 cells substantially reduced cell invasion in vitro and metastatic lung colonization in vivo, and we have shown that these phenotypes are due at least partly to the loss of α3β1-dependent gene regulation in these cells [11][12][13]. However, α3β1 also has important roles in cell adhesion and migration, raising the possibility that this integrin also promotes invasion and/or metastasis independently of its ability to regulate gene expression.…”
Section: Plos One α3β1 Promotes Breast Cancer Cell Invasion and Metastatic Colonization Independently Of Global Regulation Of The Transcrmentioning
confidence: 81%
See 3 more Smart Citations